Introduction

When the terms in a quadratic expression are written in descending order of their

respective exponents, the resulting quadratic expression is said to be in its standard

form or in its general form. The standard form (general form) of a quadratic expression

is a s follows:

ax

In the above expression, 'a', 'b' and 'c' are numbers and 'a' should not be equal

to 0, otherwise the expression will not remain quadratic (since the highest exponent

will not be equal to zero as 0x

respective exponents, the resulting quadratic expression is said to be in its standard

form or in its general form. The standard form (general form) of a quadratic expression

is a s follows:

ax

^{2}+ b + cIn the above expression, 'a', 'b' and 'c' are numbers and 'a' should not be equal

to 0, otherwise the expression will not remain quadratic (since the highest exponent

will not be equal to zero as 0x

^{2}= 0)- For example, in the following expression, a = 2, b = 3 and c = 1:

2x^{2}+ 3x + 1 - In the following quadratic expression, a = -2, b = -3 and c = -1:

-2x^{2}- 3x - 1 - In the following expression, a = 1, b = 1 and c = 1:

x^{2}+ x + 1 - In the following expression, a = 1/2, b = 1/3 and c = 1/6:

x^2/2 + x/3 + 1/6

Converting a quadratic expression to its standard form

In order to convert any quadratic expression to its standard form, you need to follow the following general steps:- Remove any parenthesis by applying distribution or FOIL, as appropriate
- Rewrite the expression in descending order of exponents

Example:

Given quadratic: | 4 + x(3 + 2x) |

Remove parenthesis by distributing x | 4 + 3x + 2x^{2} |

Rewrite the expression in descending order of exponents | 2x^{2} + 3x + 2 |